Pengembangan Multimedia Pembelajaran Computer Based Instruction (CBI) Menggunakan Adobe Flash Di SMK Negeri 10 Medan - Anjelina Taripar Nainggolan; Baharuddin Baharuddin (INCODING: Journal of Informatics and Computer Science Engineering, 2023)
The development of Computer Based Instruction (CBI) Interactive Learning Multimedia using the Adobe Flash application aims to determine the feasibility of this media as learning that is applied to Multimedia subjects for class XI SMK Negeri 10 Medan. This research is a type of development research (RD) using the ADDIE development model which has Analysis, Design, Development, Implementation, Evaluation stages. The feasibility test that will be carried out involves 2 media validators, 2 material validators and all class XI students of SMK Negeri 10 Medan. The feasibility validation instrument to be used in this study was adapted from Sriadhi's research instrument which consisted of 3 validation instruments, namely: material instruments, media instruments, and user instruments. Based on the results of the due diligence study obtained from media experts of 4.15 "decent", material experts 4.33 "very feasible", users (students) 4.21 "very feasible" this indicates that the development of Computer Based Instruction-based learning media ( CBI) using the Adobe Flash application is very feasible to apply to Multimedia subjects in class XI at SMK Negeri 10 Medan.